Slope stability and surface displacement analysis of the Kuther Landslide in the Dehar Watershed, Himachal Himalaya, Northern India - Arun Kumar; Shashi Kant Rai; Imran Khan; Manthena Prashanth; Sunil Dhar; Omkar Verma (Discover Geoscience)
Abstract The road network in the Himalayan terrain is vital for India's socio-economic development and national security, yet the complexities of topography, geological structures, diverse lithology, and neotectonics make planning and maintaining these routes a challenging task. Population growth and expanding road construction have caused slope destabilization, mass wasting, and movement across the Himalayan terrain. Field-based slope stability assessments are essential for slope mass characterization and slope stabilization, helping planners predict and select suitable construction strategies for roads and other infrastructure. This study presents a comprehensive slope stability and displacement analysis of the Kuther landslide, situated along the Jawali to Kuther road in the Dehar Watershed, Kangra District, Himachal Pradesh. An integrated approach was used, combining surface displacement monitoring with the COSI-Corr technique and slope stability assessments through methods such as rock mass rating, kinematic analysis, slope mass rating, and continuous slope mass rating. Findings indicate that the slope is highly susceptible to planar failure, with some instances of wedge failure. The rock mass ranges from class III to IV, indicating conditions from partially stable to stable, while displacement analysis reveals the slope is creeping at an average rate of 4 mm/year. This study highlights the critical need for comprehensive slope stability and displacement analyses to ensure the safety of vulnerable areas and their communities.